PERANCANGAN SISTEM INFORMASI PENDATAAN ALUMNI BERBASIS WEB (Studi Kasus: SMA Negeri 94 Jakarta) - Dandi Agih Kusdinar (2021)
The development of information technology in the field of education is used as a medium to help improve the services of educational institutions. SMAN 94 Jakarta is one of the educational institutions that collect alumni every year, but the process of alumni data collection is done manually using paper media. It is not effective and efficient to produce information. This research aims to create an information system that utilizes web facilities at SMA Negeri 94 Jakarta institutions to help record alumni. The preparation of this information system uses waterfall method. The programming languages used are HTML, PHP, and JavaScript supported with MySQL as its database. In addition, the preparation of this information system was built by utilizing a PHP framework with an MVC concept called Laravel to improve the quality of the software. The result of this study is the creation of an information system for data collection of alumni of SMA Negeri 94 Jakarta can support the process of data collection of alumni into an information material to improve the quality of education services.